Dysfunction of the foetal arterial duct results in a wide spectrum of cardiovascular pathology. Issue 6 (2nd November 2017) - Gewillig, Marc; Brown, Stephen C.; Roggen, Mieke; Eyskens, Benedicte; Heying, Ruth; Givron, Patrice; Cools, Bjorn; de Catte, Luc
Abstract: Objective: Foetal ductal problems may have various cardiopulmonary consequences. This study aimed to identify the spectrum of ductus arteriosus (DA) dysfunction (closure, constriction, kinking, aneurysm and thrombosis) and the resultant clinical and echocardiographic presentation in foetuses and neonates. Methods and results: This is a retrospective analysis of serial pre- and post-natal data of 27 cases of foetal ductal dysfunction diagnosed at a median gestational age of 33 weeks (range 20–39). The most common abnormalities observed were premature closure of the DA in 56% (15/27) and constriction in 29% (8/27). Right ventricular hypertrophy was present in 75% ( n = 11/15) of foetuses with premature DA closure, while ventricular dilation (4/7, 57%) was a more common feature in foetuses with ductal constriction. After birth, 63% (17/27) of new borns presented with cyanosis and pulmonary hypertension that required active treatment. Three infants died after birth. Abnormalities resolved spontaneously after birth in about 50% of patients. In some children, pulmonary valve stenosis and regurgitation was progressive and required further treatment. Conclusions: An abnormal right heart on foetal four-chamber ultrasound view should alert the sonographer to the possible presence of foetal ductal dysfunction. Ductal occlusion, transient or fixed constriction, kinking and aneurysm formation are associated with foetal cardiopulmonary sequelae. Symptoms and pathology is probably related to the type, foetal age, rapidity of progression and duration of intrauterine ductal dysfunction. Correspondingly, clinical outcomes vary ranging from little or no symptoms to severe respiratory distress and even foetal or neonatal death.